(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Based on the digitalization of the national insurance market of Uzbekistan, the offered insurance services related to the issues of managing insurance companies were considered. In this, the experience of the insurance market of developed countries and the insurance companies that are its participants was used. Thoughts on making effective management decisions based on a complete analysis of the competitiveness and financial stability of insurance companies are expressed.